Constructivist Analytics: Using Data to Enable Deeper Museum Experiences for More Visitors—Lessons from the Learning Sciences. Issue 1 (2nd January 2017) - Berland, Matthew
ABSTRACT: This article defines and outlines constructivist analytics, a framework for understanding how, where, and when the narratives we construct with advanced data analysis can affect positive social change in informal learning environments (such as museums). I ask three core questions based on this framework: How can researchers use analytics to understand what different visitors find valuable? How can we use analytics to help more visitors find value and to improve visitors' experiences when they find value? How can we present and structure analytics in ways that many different stakeholders find valuable? I then suggest possible avenues for both expanding current work in constructivist analytics and developing new angles on positive, effective, and data-rich narratives.